2011
DOI: 10.2151/jmsj.2011-510
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Impacts of Two-Type El Nino over the Western North Pacific during Boreal Autumn

Abstract: This work contrasts the climatic impacts of so-called warm-pool (WP) and cold-tongue (CT) El Niño on the atmospheric circulation over the western North Pacific (WNP). It is found that the anomalous atmospheric circulation over the WNP is nearly opposite in response to these two types of El Niño events in developing autumn. A weak anomalous anticyclone appears over the WNP during CT El Niño, whereas a weak anomalous cyclone emerges in the same region during WP El Niño. These nearly opposite autumn responses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
110
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 133 publications
(127 citation statements)
references
References 24 publications
14
110
2
1
Order By: Relevance
“…W. concluded that strong El Niño events are associated with summer monsoon flooding over the Yangtze River, which is consistent with our results. The distribution of rainy-season precipitation for developing El Niño is also in agreement with the research by Zhang et al (2011). Northern China had an opposite PARS pattern for developing El Niño Modoki, in comparison to developing CEN (Fig.…”
Section: Precipitation Anomaly During Rainy Season (Pars) Impacted Bysupporting
confidence: 89%
See 1 more Smart Citation
“…W. concluded that strong El Niño events are associated with summer monsoon flooding over the Yangtze River, which is consistent with our results. The distribution of rainy-season precipitation for developing El Niño is also in agreement with the research by Zhang et al (2011). Northern China had an opposite PARS pattern for developing El Niño Modoki, in comparison to developing CEN (Fig.…”
Section: Precipitation Anomaly During Rainy Season (Pars) Impacted Bysupporting
confidence: 89%
“…Gerlitz et al (2016) argued that ENSO-induced precipitation variability in tropical regions is directly associated with the atmospheric circulation. The atmospheric circulation and monsoon have different influences on two types of ENSO (Feng and Li, 2013;Zhang et al, 2011;Zhou and Chan, 2007). As a consequence, the investigation of atmospheric circulation and monsoon is used to explain different performance of rainy-season precipitation anomalies under various ENSO regimes in this study.…”
Section: Introductionmentioning
confidence: 99%
“…All of them emphasize the important role of the anomalous western North Pacific anticyclone. The first one mentions the equatorial Rossby wave response to ENSO via the Pacific-East Asia teleconnection (Wang et al, 2000;Zhang et al, 2011;Karori et al, 2013;Feng et al, 2016). The second one is related to an equatorial Kelvin wave response to Indian Ocean warming during El Niño decaying summer, which is named "Indian Ocean capacitor effect" (Xie et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies revealed that the CP type of El Niño has significantly different global climate impacts from the EP El Niño through tropical-extratropical teleconnections (e.g., Weng et al 2007Weng et al , 2009; Kim et al 2009;Feng et al 2010;Feng and Li 2011;Zhang et al 2011Zhang et al , 2012Yuan and Yang 2012) as these two types of El Niño are accompanied with distinct tropical atmospheric circulations. La Niña events, the negative phase of ENSO events, are usually less distinguishable in terms of the two types (Kug and Ham 2011).…”
Section: Introductionmentioning
confidence: 99%